A Study on the Mediating Effect of Financial Literacy Between Personality Traits and Irrational Buying Behaviors - Mehmet Ali Paylan; Yusuf Bahadır Kavas (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
This study aims to test whether financial literacy, which is one of the most studied topics in behavioral finance in recent years, affects compulsive and impulsive buying behavior. It also aims to answer whether financial literacy mediates the relationship between personality traits and compulsive and impulsive buying behavior. The population consists of people over the age of 18 residing in Turkey. Data were collected using an online questionnaire from 405 participants selected by convenience sampling from this population. To test the hypothesis, data were subjected to regression and mediation analysis. The results show that financial literacy has a significant effect on compulsive and impulsive buying behavior and also type A and B personality has a significant effect on financial literacy. On the other hand, Financial literacy doesn’t mediate between A and B personality typologies and compulsive and impulsive buying behaviors. In future studies, especially if financial literacy is measured on a continuous scale, the research model might be show more significant results in terms of mediation effect. Based on the findings, the increase in the level of financial literacy may positively affect the saving tendencies of individuals. Thus, individuals will be prevented from compulsive and impulsive buying behaviors. This study is original as it is the first research in the literature that examines financial literacy and irrational buying behaviors together.